PENGARUH VIDEO ANIMASI NUSSA DAN RARA TERHADAP KEMAMPUAN MENYIMAK - Hamimah; Nadar, Wahyuni; Andi Musda Mappapoleonro (Al Hanin, 2025)
This research aims to describe the influence of the animated video media nussa and rara eps. Learning for listening skills. The research method used is quasi-experimental. This research was conducted at RA Nursyamsi in Depok city. The sample in this study consisted of two groups, namely the experimental group of 18 students and the control group of 18 students. The experimental group was the group that carried out learning using animated video media Nussa and Rara, while the control group was the group that used story books. The assessment instrument used is a listening test instrument. Based on the results of the t-test on the experimental class posttest data with a significance level of 0.05%, tcount = 20.144 which means the alternative hypothesis Ha is accepted Ho is rejected Ha is accepted. This means that there is an influence of nussa and rara animated video media on listening ability.